How Brand Trust is Influenced by Perceived Value and Service Quality: Mediated by Hotel Customer Satisfaction - Adelia Shabrina Prameka; Ben-Roy Do; Ainur Rofiq (Department of Management, Faculty of Economics and Business, Brawijaya University, 2016)
This paper examines the effect of perceived value and service quality on brand trust directly and indirectly through customer satisfaction. Brand trust can be defined as the relationship between consumers and the corporate that is based on trust and reliability of its performance. Questionnaires were given to guests of three-star hotels in Malang, Indonesia, with 158 surveys returned and 114 valid responses were analyzed. Reliability and validity were examined first, and partial least squares (PLS-SEM) analysis was performed to evaluate the determinant coefficient (R2), predictive relevance (Q2), and effect size (f2). Results showed customer satisfaction partially mediates perceived value on brand trust, and fully mediates the relationship between service quality and brand trust. Future research in other developing countries, against different hotel class, with international guests, is recommended. Managerial implications were discussed.